Code for ML reconstruction of surface ocean pCO2 using the Large Ensemble Testbed - Heimdal, Thea H.; McKinley, Galen; Sutton, Adrienne; Fay, Amanda; Gloege, Lucas; BENNINGTON, VAL (Zenodo, 2024)
This repository contains code used for the study "Assessing improvements in global ocean pCO2 machine learning reconstructions with Southern Ocean autonomous sampling" (Heimdal et al., 2023, https://doi.org/10.5194/bg-2023-160). In this paper, we reconstruct surface ocean pCO2 using the Large Ensemble Testbed (Gloege et al., 2021) and the pCO2-Residual method (Bennington et al. (2022), and test the effect of additional sampling in the Southern Ocean.